Market Chickens as a Source of Antibiotic-Resistant Escherichia coli in a Peri-Urban Community in Lima, Peru - Murray, Matthew; Salvatierra, Guillermo; Dávila-Barclay, Alejandra; Ayzanoa, Brenda; Castillo-Vilcahuaman, Camila; Huang, Michelle; Pajuelo, Mónica J.; Lescano, Andrés G.; Cabrera, Lilia; Calderón, Maritza; Berg, Douglas E.; Gilman, Robert H.; et al. (Frontiers in Microbiology, 2021)
The widespread and poorly regulated use of antibiotics in animal production in low- and middle-income countries (LMICs) is increasingly associated with the emergence and dissemination of antibiotic resistance genes (ARGs) in retail animal products. Here, we compared Escherichia coli from chickens and humans with varying levels of exposure to chicken meat in a low-income community in the southern outskirts of Lima, Peru. We hypothesize that current practices in local poultry production result in highly-resistant commensal bacteria in chickens that can potentially colonize the human gut. E. coli was isolated from cloacal swabs of non-organic (n=41) and organic chickens (n=20), as well as from stools of market chicken vendors (n=23), non-vendors (n=48) and babies (n=60). 315 E. coli isolates from humans (n=150) and chickens (n=165) were identified, with chickens showing higher rates of multidrug-resistant and extended-spectrum beta-lactamase phenotypes. Non-organic chicken isolates were more resistant to most antibiotics tested than human isolates, while organic chicken isolates were susceptible to most antibiotics. Whole-genome sequencing of 118 isolates identified shared phylogroups between human and animal populations and 604 ARG hits across genomes. Resistance to florfenicol (an antibiotic commonly used as a growth promoter in poultry but not approved for human use) was higher in chicken vendors compared to other human groups. Isolates from non-organic chickens contained genes conferring resistance to clinically relevant antibiotics, including mcr-1 for colistin resistance, blaCTX-M ESBLs, and blaKPC-3 carbapenemase. Our findings suggest that E. coli strains from market chickens are a potential source of ARGs that can be transmitted to human commensals.